Analisis Aspek-Aspek Perkreditan dalam Pemborongan Bangunan - Ramadhan, Arif; Risnawati, Risnawati; Utami, Silvi Agustina; Afdaruqutni, Yoepi; Yola, Yola; Syaputra, Didi (Indra Institute Research & Publication, 2024)
Credit in the building contracting industry plays an important role in achieving project success and protecting the interests of banks and related parties. Careful credit evaluation, use of appropriate collateral, effective credit management, and the bank's active role in supervising project progress are key factors in building contractor loans. In addition, effective dispute resolution, attention to risk factors, and integration of environmental aspects are also important in maintaining the smooth running of building contracts. By complying with applicable legal regulations, banks can carry out credit activities in a trusted manner, protect the interests of related parties, and ensure the economic and environmental sustainability of projects.